2014
DOI: 10.1155/2014/706439
|View full text |Cite
|
Sign up to set email alerts
|

Severe Growing-Up Phobia, a Condition Explained in a 14-Year-Old Boy

Abstract: We present the clinical case of a 14-year-old boy with gerascophobia or an excessive fear of aging, who felt his body development as a threat, to the point where he took extreme measures to stop or otherwise hide growth. He had a history of separation anxiety, sexual abuse, and suffering bullying. He presented with anxious and depressive symptoms and food restriction, criticized his body image, had negative feelings towards the maturation process, suffered at the thought of being rejected, and was preoccupied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Studies have shown that gerascophobia is associated with harmful health consequences such as the increased risk of chronic diseases including cardiovascular problems and depression (8,10,11). For example, a 14-year-old boy perceived his body's growth as a threat due to his fear of aging, to the extent that he took drastic measures to stop growth, such as restricting what he ate, and showed negative attitudes toward puberty (12).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that gerascophobia is associated with harmful health consequences such as the increased risk of chronic diseases including cardiovascular problems and depression (8,10,11). For example, a 14-year-old boy perceived his body's growth as a threat due to his fear of aging, to the extent that he took drastic measures to stop growth, such as restricting what he ate, and showed negative attitudes toward puberty (12).…”
Section: Introductionmentioning
confidence: 99%
“…Excessive fears will be a symptom of phobias that adversely affect the quality of life (Theofilou, 2013;Jarymowicz & Bar-tal, 2006). Decreased quality of life certainly has an influence on stress and mental disorders which are considered as risk factors that correlate to the subsequent development of mental disorders and other illnesses with consequences such as anxiety disorders, panic, depression, mood affective disorders, insomnia, parkinsonism, heart disease, decreased appetite, gastric pains, migraines, infectious diseases, drug abuse, drug dependence, and worse, suicide attempts (Safren, 1996;Fahlen, 1996;Lichtenberg, 1991;Pitkanen et al, 2009;Perales et al, 2014).…”
Section: Introductionmentioning
confidence: 99%